2017
DOI: 10.5897/ijnm2017.0258
|View full text |Cite
|
Sign up to set email alerts
|

Practice of child spacing and its associated factors among women of child bearing age (15 to 49 years) in Illubabor zone, South West Ethiopia

Abstract: Optimal birth spacing refers to resting period between pregnancies that allows the mother time to recuperate from pregnancy, labor and lactation. Long time period between births allows the next pregnancy and birth to be at full gestation and growth for years. This study aimed to assess practice of child spacing and its associated factors among women of child bearing age in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 5 publications
6
12
0
Order By: Relevance
“…Mothers with primary school level of education in this study were less likely to practice suboptimal birth spacing than those who cannot read and write. This finding is consistent with 2016 Ethiopian Demographic and Health Survey (EDHS) report 22 and with reports of different studies conducted in Southern Ethiopia, 1 Illubabor zone, South West Ethiopia, 23 Ghana, 24 South Jordan, 16 and Manipur, India. 25 This is probably because education affects the reproductive decisions of women as it positively affects women's understanding and/or knowledge of contraception and birth spacing as well as their health-seeking behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mothers with primary school level of education in this study were less likely to practice suboptimal birth spacing than those who cannot read and write. This finding is consistent with 2016 Ethiopian Demographic and Health Survey (EDHS) report 22 and with reports of different studies conducted in Southern Ethiopia, 1 Illubabor zone, South West Ethiopia, 23 Ghana, 24 South Jordan, 16 and Manipur, India. 25 This is probably because education affects the reproductive decisions of women as it positively affects women's understanding and/or knowledge of contraception and birth spacing as well as their health-seeking behavior.…”
Section: Discussionsupporting
confidence: 90%
“…However, a higher likelihood of practicing short birth interval was noticed among women in the highest wealth quartile in Lemo district, southern Ethiopia 1 and Illubabor zone, South West Ethiopia. 23 A lesser likelihood of practicing subsequent short interbirth interval was observed among mothers who utilized post-natal care than their counterparts who did not use. This is probably because these mothers have the chance to be counseled about birth spacing and contraception and the timely use of contraceptive methods.…”
Section: Discussionmentioning
confidence: 98%
“…Mothers who breastfed their preceding child for at least 24 months had lower odds of short birth interval than those who breastfed for less than 12 months. This finding was supported by different studies which revealed lengths of birth interval to be influenced by duration of breastfeeding [ 26 – 28 ].Moreover, studies in Arba Minch District [ 20 ] and four disadvantaged regions of Ethiopia [ 21 ] showed similar finding which may be attributed to the fact that breast feeding has contraceptive effect due to the negative hormonal feedback mechanism of the hypothalamic-pitutary-ovarian axis. On the contrary, according to a community based cross sectional study in Southern Ethiopia, longer duration of breast feeding was significantly associated with increased incidence of short birth interval [ 22 ].The discrepancy might be due to differences in breast-feeding practices (exclusive breastfeeding, duration and frequency of breast feeding per 24 hours) and maternal factors (age, parity, nutritional status) [ 12 ] between the two studies.…”
Section: Discussionmentioning
confidence: 74%
“…However, different results show that there are areas with high incomes indicating short birth intervals (Ajayi and Somefun, 2020). This is because mothers with the lowest income levels will be busy in their activities to earn extra income to meet their daily needs as a result they will delay their pregnancy (Dereje, Muluneh and Kebebe, 2017). The economic level is not enough to change the mindset to regulate birth intervals, the appropriate birth intervals can be supported by the existence of high education to support rational thinking, and the desire to plan for future pregnancies using contraception.…”
Section: Discussionmentioning
confidence: 99%